Efektivitas Edukasi Kesehatan Tentang Polycystic Ovary Syndrome (PCOS) Melalui Media Sosial Terhadap Pengetahuan dan Sikap Remaja Putri di Madrasah Aliyah Laboratorium Jambi - Oktavia, Risa; Lanita, Usi; Siregar, Sri Astuti; Reskiaddin, La Ode; Perdana, Silvia Mawarti (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2024)
Polycystic Ovary Syndrome (PCOS) is one of the main causes of infertility in reproductive age women. Around 17.5% of the adult population, 1 in 6 worldwide experience infertility. This research aims to analyze the effectiveness of health education about PCOS using social media on the knowledge and attitudes of young women at the Madrasah Aliyah Laboratorium Jambi. Quantitative research with a Quasi Experimental design, Pre-test and Post-test Non-Equivalent Control Group design. The total sample was 25 people, with 14 people in the Instagram social media intervention group and 11 people in the Facebook intervention group. The social media Instagram and Facebook are effective in increasing knowledge of young women before and after on Instagram (p=0.000) and Facebook (p=0.000). On the attitudes of young women before and after on Instagram (p=0.001) and Facebook (p=0.009). Meanwhile, there is no significant difference in effectiveness between Instagram and Facebook in PCOS health education on knowledge (p=0.513) and attitudes (p=0.057) of young women at Madrasah Aliyah Laboratorium Jambi. There were differences in knowledge and attitudes before and after the Instagram and Facebook intervention, and there was no significant difference in effectiveness between Instagram and Facebook in PCOS health education on the knowledge and attitudes of young women at Madrasah Aliyah Laboratotium Jambi. Young women are advised to be more concerned about reproductive health because information can be obtained in various media, especially social media. Keywords: PCOS, Instagram, Facebook, Knowledge, Attitude